Viscoelastic behavior of high molecular weight polyimide/cyclohexanone solution during sol-gel transition. (2nd March 2020) - Chen, Hongxiang; Liu, Wei; Hong, Mei; Zhang, Ensong; Dai, Xuemin; Qiu, Xuepeng; Ji, Xiangling
Abstract: It is very important to optimize rheological properties of polyimide (PI) solution for film casting or fiber spinning. Herein, a soluble 2, 2-bis(3, 4-di-carboxyphenyl) hexafluoro propane dianhydride-2, 2′-bis(trifluoromethyl)-4, 4′-diaminobiphenyl PI sample with high absolute molecular weight of 390, 000 g/mol was obtained by precipitation fractionation. The viscoelastic behavior of PI in cyclohexanone solution was investigated at different concentrations (0.1–12 wt%). PI gel can form at a suitable concentration. Analysis of viscoelastic storage and loss moduli, G ' and G ' ', based on the Winter and Chambon model gives the gel concentration c g = 4 wt% and the critical relaxation exponent n = 0.56. The scaling relations such as zero-shear viscosity η 0 and equilibrium modulus G e against relative distance from the gel point ε, that is η 0 ∝ ε − γ and G e ∝ ε z, were examined in the vicinity of c g, where a fractal dimension d f = 2.54 indicates formation of a compact gel structure. Addition of N, N-dimethylformamide (DMF) strongly decrosslinks the PI solution, suggesting a screening of the interchain dipole–dipole interactions by the highly polar DMF solvent. Graphical abstract: Image 1 Highlights: Rheological investigation on the viscoelastic behavior of polyimide/cyclohexanone solution. Study the gelation behavior based on the Winter and Chambon model. Effects of solvent quality on solution properties; adding DMF can destroy gel structure.